1996
DOI: 10.1093/oxfordjournals.humrep.a019196
|View full text |Cite
|
Sign up to set email alerts
|

Uterus and endometrium: Immunohistochemical localization of extracellular matrix proteins in luteal phase endometrium of fertile and infertile patients

Abstract: The lack of expression of certain components involved in cell adhesion and migration is believed to contribute to endometrial dysfunction and implantation failure. The purpose of this study was to investigate whether luteal phase endometrium in women with unexplained infertility differs, with respect to specific extracellular matrix (ECM) proteins, from endometrium of normal fertile women. A panel of monoclonal antibodies to collagen type IV, fibronectin and laminin was used to characterize the localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 12 publications
1
21
0
2
Order By: Relevance
“…Remodeling of the endometrial extracellular matrix, mediated by an altered balance of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs), is indispensable for successful implantation and placentation, and has been well described in humans and rodents (Farrar and Carson, 1992;Clark et al, 1993;Das et al, 1997;Hurst and Palmay, 1999). Defects in the distribution of certain ECM glycoproteins have been implicated in implantation failure in women suffering from unexplained infertility (Bilalis et al, 1996) and functional studies using MMP inhibitors…”
Section: Remodeling Of the Ecm At Implantationmentioning
confidence: 99%
“…Remodeling of the endometrial extracellular matrix, mediated by an altered balance of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs), is indispensable for successful implantation and placentation, and has been well described in humans and rodents (Farrar and Carson, 1992;Clark et al, 1993;Das et al, 1997;Hurst and Palmay, 1999). Defects in the distribution of certain ECM glycoproteins have been implicated in implantation failure in women suffering from unexplained infertility (Bilalis et al, 1996) and functional studies using MMP inhibitors…”
Section: Remodeling Of the Ecm At Implantationmentioning
confidence: 99%
“…These ECM components were also reported to regulate trophoblast proliferation and differentiation during pregnancy (7)(8)(9)(10). Furthermore, abnormal expression of these ECM components in the endometrium was reported in a patient, infertile from an unknown cause (1).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, remodeling of the functional human endometrium must involve the cyclic production of extracellular matrix (ECM) that occupies the intercellular spaces in addition to cell regeneration and proliferation. Laminin and type IV collagen (COL-4) are well-known major components of epithelial basement membranes in the human body, and have been reported to localize in the basement membrane structure of human endometrial epithelium (1,2). Several studies have shown that these ECM components are produced at a high level in human deciduas (3,4), while laminin was reported to inhibit endometrial stromal decidualization (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Laminin has been reported to inhibit endometrial stromal differentiation (6,7), while both laminin and COL-4 have been found to regulate trophoblast proliferation and differentiation during pregnancy (8)(9)(10)(11). Furthermore, abnormal expression of these ECM components in the endometrium was reported in a patient with unexplained infertility (1). We recently demonstrated that laminin and COL-4 regulated normal human endometrial stromal remodeling in an autocrine/paracrine fashion during the menstrual cycle (5).…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling of the functional human endometrium must involve cyclic production of extracellular matrix (ECM), as well as cell regeneration and proliferation. Laminin and type IV collagen (COL-4) are well-known major components of epithelial basement membranes in the human body and have been reported to localize in the basement membrane-like structures (BM-like-S) of human endometrial epithelium (1,2). Several studies have shown that both these ECM components are highly expressed in human endometrial stromal cells and deciduas (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%